The Socio-Textual Values approached in the Critical Discourse Analysis of Donald Trump's Recognition Speech of Jerusalem as Israel's Capital - Adeeb, Eman Riyadh (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
The recent study aims at investigating the interrelation of discourse structures and hidden ideological structures behind the use of certain words in a language through Critical Discourse Analysis in Donald Trump's speech of regarding Jerusalem as Israel's capital at December 6, 2017 on Wednesday. In this venue, the study unmasks the inserted, hidden ideologies and deposits the most real intensions and ideas behind the utterances delivered. Thus, use of some specific words is not generally unbiased, but it has a positive or negative colour on them. The effort made is to find out the truth hidden behind Trump's speech on the major and general issue of announcing Jerusalem as Israel's capital and some chunks about their relation with other world countries. Doubtlessly, the recognition of Jerusalem as an Israel's capital and the move of the U.S embassy are regarded as one of the most sensitive issues in the world especially the Middle East then. Here, the research analyzes and uncovers the experiential, relational and expressive values of the wording, rewording, overwording along with the grammatical structures and the functional values they add to the utterance.